Antibiotic Resistance Among Coliform and Fecal Coliform Bacteria Isolated from the Freshwater Mussel Hydridella menziesii - Cooke, Marylyn D. (1976)
Freshwater mussels (Hydridella menziesii) collected from Lakes Rotoroa, Rotoiti, and Brunner, South Island, New Zealand, contained coliform and fecal coliform bacteria. The majority of these bacteria were resistant to one or more antibiotics, but none transferred streptomycin, tetracycline, or kanamycin resistance to an antibiotic-susceptible strain of Escherichia coli K-12.